Pengecualian Rahasia Bank Bagi Kurator Melalui Putusan Pengadilan Niaga Berdasarkan Undang-Undang Nomor 4 Tahun 2023 - Abdul Aziz (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Bankruptcy is a situation where a debtor is unable to pay their debts to their creditors. If a debtor is declared bankrupt by a court, the administration of the bankrupt assets will be carried out by a curator. The purpose of bankruptcy is to pay the rights of creditors in a certain order. However, the task of the curator is not always easy because there are several obstacles such as uncooperative debtors or conflicting laws and regulations, such as bank secrecy regulated in the Banking Law and the Bankruptcy and PKPU Law. As an example, in Ryan Gunawan Lubis' thesis titled